The Effect of Torbangun Leaves Tea on Msg-induced Fetal Develop-ment Disorder in Mice - M.Kes, Sufitni; Feriyawati, Lita; Pane, Yunita Sari; Lelo, Aznan (Talenta Publisher, 2019)
The safety of MSG on the fetus has not been confirmed yet. The objective of this research is to determine the effect of tea of torbangun leaves on fetal development disorder of mice. The present study is experimental with a Completely Randomized Design (CRD). Data obtained were then analyzed by ANOVA, with p<0,05 as the level of significant. The comparison of mean values ± SEM increase number of live fetuses group C1-T1 (4,60 ± 0,93; 11,40 ± 0,87), p=0,018. The comparison of mean values ± SEM decrease number of embryo re-sorption percentage group C0-C1 (00,00 ± 00,00; 36,74 ± 15,13), group C1-C2 (36,74 ± 15,13; 00,00 ± 0,00), group C1-T1 (36,74 ± 15,13; 00,00 ± 0,00), and group C1-T2 (36,74 ± 15,13; 15,00 ± 22,36), p=0,020. This study concluded that T1 group is giving the best effect on increasing life fetuses and decreasing embryo re-sorption percentage.